Behavior of stainless steels against electrochemical corrosion - Dionicio Padilla, Eusebio (1998)
The present investigation of potential metric techniques in the determination of the corrosion rate of AISI 304 stainless steel, has been possible through the use of the potentiostat that has a measurement range of 0.005 mA to 1,000 mA with responses in the potentials of 0.1 at 100 mV. The corrosion rates of AISI 304 stainless steel have been determined: medium: 3.56% C.R. sodium chloride solution. (mpy) = 1.72 medium: synthetic sea water C.R. (mpy) = 1.28. The study of corrosion rate measurement in engineering material, using the potentiostat has proven to be fast and reliable.